A low-cost digital-domain foreground calibration for high resolution SAR ADCs. (March 2018) - Guan, Rui; Jin, Jing; Zhou, Jianjun
Abstract: A digital-domain foreground calibration method simultaneously correcting mismatch errors in main capacitive digital to analog converter (CDAC) and "segment error" between main CDAC and sub-CDAC of split-CDAC array in high resolution successive approximation register (SAR) analog-to-digital converter (ADC) is proposed. The actual weight is obtained with the digital-domain weight estimation algorithm. This proposed digital-domain calibration saves silicon area by eliminating the need for a dedicated calibration DAC employed in conventional CDAC mismatch calibration schemes. Behavioral simulation shows the proposed calibration is capable of correcting mismatch errors and "segment error" of split-CDAC array, and improving SNDR from 67.3 dB to 92.8 dB in a prototype 16 bit split-CDAC SAR ADC.